Efektivitas Lubang Resapan Organopori Dalam Menahan Laju Erosi Dan Stabilitas Ekologi Tanah Pada Aliran Das Citarum, Dusun Tujuh, Desa Mulyasejati, Kabupaten Karawang, Jawa Barat - Rahmayanti, Fetty Dwi; Diana, Tungga Buana; Husni, Husni (universitas wiralodra, 2020)
Tujuh Village is geographically intersected with Citarum watersheds and according to the Regional Government of West Java Province (2019); this village is one of the areas prioritized by the government to become a land and water conservation area in the national program of